Development and implementation of a multifaceted well-being intervention. Issue 4 (5th December 2016) - Mills, Maura J.; Fullagar, Clive J.; Culbertson, Satoris S.
Abstract : Purpose: The purpose of this paper is to develop and implement an intervention to increase individuals' hedonic well-being (HWB) and/or eudaimonic well-being (EWB) via cognitive reframing and action-based behaviors. Design/methodology/approach: Time 1 and Time 2 data were collected two weeks apart from 76 participants (comprised of city employees, extension agents, and students) in an intervention group (23) and a characteristically similar control group (53). The intervention included an in-person facilitated meeting with a series of follow-up e-mails designed to focus participants on well-being improvement strategies and provide them resources for continued well-being development. Findings: Intervention participants evidenced a significant increase in EWB after two weeks, particularly the personal growth dimension. No significant increase resulted for HWB. Research limitations/implications: The present intervention indicates the importance of targeting well-being at a facet level, including a focus on multidimensional EWB. The intervention also serves to guide the informed development of future well-being programs. Practical implications: These findings have important implications for organizations in light of increased employee desire for personal and professional growth opportunities supported by their employer. Group interventions such as the one reported herein are an important way for organizations to develop and invest in employees. Originality/value: This paper traces the development of prior well-being interventions, evaluating their successes and failures and using those to guide the informed development of the present intervention. By utilizing both in-person and follow-up components, and incorporating both hedonic and multidimensional eudaimonic components, the proposed intervention serves as an important step toward a feasible organizational intervention that can benefit many.